BE SURE THE STUDENT’S ENGLISH GRAMMAR MASTERY ON SPEAKING SKILL BY COMMUNICATIVE ASESSEMNT MODEL - Sinaga, Yusni (AIN Padangsidimpuan, 2014)
This article has the purpose to describe the way of lecture to assess his or her student’s English grammar by implementation of Communicative Assessment Model, and to inform the advantages of the implementation of the Communicative Assessment Model.